A comparative study of grammar achievement between male and female students - Baiqun Isbahi; Eduardo Mendoza (Journal of Research in English Language Teaching and Linguistics, 2025)
Grammar mastery is crucial for effective language acquisition and communication, especially in English as a Foreign Language (EFL) context. Recent studies show notable disparities in grammar achievement between male and female learners, but there is limited research focusing specifically on these differences within structured educational settings. This study aims to explore the comparative grammar achievement of male and female junior high school students in East Java, Indonesia, addressing the gap in understanding gender-specific learning outcomes. A comparative research design was employed, involving 60 ninth-grade students from a single public school, evenly divided by gender. Data collection involved administering a validated multiple-choice grammar test, assessing key grammatical concepts aligned with the national curriculum. The test's reliability was confirmed through a pilot study, and results were analyzed using SPSS, employing independent samples t-tests to determine the significance of gender differences in performance. Findings indicate that female students significantly outperformed their male counterparts in grammar achievement, with a higher average score and greater consistency. This disparity suggests the potential influence of gender-related factors in learning strategies and outcomes. The study underscores the necessity for educators to adapt instructional methods to accommodate diverse learner profiles, thereby promoting equitable educational experiences. Furthermore, it highlights the importance of addressing gender dynamics in grammar instruction, encouraging future research on tailored teaching practices that enhance learning outcomes for all students. Overall, this study contributes to the understanding of gender differences in EFL grammar achievement and calls for reconsideration of teaching methodologies to foster a more inclusive learning environment.